Compliance with Advisory Opinions in the Inter-American Human Rights System (2023)
In this essay, we analyze how different actors contribute to compliance with the advisory jurisdiction of the Inter-American human rights system. The essay briefly reviews the discussion around the binding force of, and compliance with, advisory opinions. It then analyzes how the holdings in advisory opinions issued by the Inter-American Court of Human Rights (IACtHR or Court) over the last forty years have had a notable impact on states and how different interstate actors, including the executive, the legislature, the national judiciary, and local regulatory bodies, ensure compliance.